Characterization of blood mimicking fluid with ultrafast ultrasonic and optical image velocimeters. (1st July 2022) - Omura, Masaaki; Nagaoka, Ryo; Yagi, Kunimasa; Yoshida, Kenji; Yamaguchi, Tadashi; Hasegawa, Hideyuki
Abstract: A blood mimicking fluid (BMF) is imperative for the evaluation of Doppler ultrasound. Doppler ultrasound still causes errors due to some artifacts such as aliasing and presence of grating lobes. One of the other velocimeters is the optical particle image velocimeter (PIV). This study initially developed an in vitro measurement system for analyzing flowing BMF with ultrasonic and optical PIVs. The acoustic properties such as speed of sound, attenuation, and backscatter coefficient of BMF equivalent to the human blood, used for both ultrasonic and optical PIVs were analyzed in a frequency range of 4–12 MHz. The velocity profiles were estimated by ultrasonic and optical PIVs using a block matching method. A difference between velocities obtained by ultrasonic and optical data was within 4.0% using BMF with 20 μ m polyamide particle at 0.2% concentration that realized the acoustic properties and speckle patterns similar to those in ultrafast ultrasound blood flow imaging.